A Critical Study on William Golding’S Novel ‘Lord of the Flies’: Exploring the Dark Side of Human Nature in William Golding's 'Lord of the Flies' (Journal of Advances and Scholarly Researches in Allied Education, 2013)
In Lord ofthe Flies, British schoolboys are stranded on a tropical island. In anattempt to recreate the culture they left behind, they elect Ralph tolead, with the intellectual Piggy ascounselor. But Jack wantsto lead, too, and one-by-one, he lures the boys from civility and reason to thesavage survivalism of primeval hunters. In Lord of the Flies, WilliamGolding gives us a glimpse of the savagery that underlies even the mostcivilized human beings.